Delivery of Gold Nanoparticles Inside Carbon Nanotubes by Oligonucleotides - Daxiang Cui; Cengiz S. Ozkan; Furong Tian; Yong Kong (Nano Biomedicine and Engineering, 2011)
Delivery of gold nanoparticles with 2 nm or so in diameter inside multiwall carbon nanotubes (MCNTs) by oligonucleotides was performed under the condition of 400 k and 3 bar for 20 min. The Au-oligo-CNT complexes were first purified via 1% agarose gel electrophoresis and then analyzed via high resolution transmission electron microscopy (HR-TEM) and energy dispersive X–ray spectroscopy (EDX). The results showed that the excess of oligonucleotides, Au nanopartilces and the Au-oligo hybrids attached to the outside walls of CNTs could be removed away by agarose gel electrophoresis. HR-TEM and EDX results demonstrated that 2% or so Au-oligo hybrids were successfully delivered inside MCNTs. In contrast, few Au nanopartilces were observed to locate inside CNTs under identical experimental conditions. This is the very first confirmation that oligonucleotides can be used to deliver Au nanoparticles inside MCNTs. The van der Waals attraction between CNT and Au-oligo hybrids is likely the main driving force for this phenomenon. This phenomenon has potential applications in future nanotechnology such as molecular electronics, biochemical sensors, nano-devices, gene storage and delivery systems.